Burnout and Work-Life Balance: Addressing Gender Disparities and Institutional Support - Adiawaty, Susi; Cahyono, Maria Yuni Megarini (Sinergi International Journal of Psychology, 2024)
Work-life balance is a critical factor influencing employee well-being, job satisfaction, and workforce retention. This study explores the systemic challenges associated with work-life balance, particularly in high-pressure professions such as healthcare. A systematic literature review was conducted using Scopus, Google Scholar, and PubMed to analyze research related to work-life balance, occupational stress, and employee support systems. The findings reveal a strong correlation between institutional policies, organizational culture, and the prevalence of burnout, with gender disparities playing a significant role in work-life integration challenges. Empirical evidence highlights that professionals in developed nations benefit from structured workplace policies, while employees in developing regions face more significant work-life conflicts due to limited institutional support. Organizational flexibility, mental health resources, and gender-equitable policies emerge as crucial factors in mitigating these challenges. Addressing work-life balance requires strategic interventions, including promoting workplace flexibility, enhancing mental health initiatives, and fostering cultural shifts that support work-life integration. This study underscores the necessity for continued research on long-term policy effectiveness and the impact of emerging workplace technologies on work-life balance. By implementing structured and inclusive policies, organizations can create a sustainable and productive workforce that benefits both employees and institutions.